Elemental Sulfur Formation by Sulfuricurvum kujiense Is Mediated by Extracellular Organic Compounds - Cron, Brandi; Henri, Pauline; Chan, Clara S.; Macalady, Jennifer L.; Cosmidis, Julie (Frontiers in Microbiology, 2019)
Elemental sulfur (S(0)) is a central and ecologically important intermediate in the sulfur cycle, which can be used by a wide diversity of microorganisms that gain energy from its oxidation, reduction, or disproportionation. S(0) is formed by oxidation of reduced sulfur species, which can be chemically or microbially mediated. A variety of sulfur-oxidizing bacteria can biomineralize S(0), either intracellularly or extracellularly. The details and mechanisms of extracellular S(0) formation by bacteria have been in particular understudied so far. An important question in this respect is how extracellular S(0) minerals can be formed and remain stable in the environment outside of their thermodynamic stability domain. It was recently discovered that S(0) minerals could be formed and stabilized by oxidizing sulfide in the presence of dissolved organic compounds, a process called S(0) organomineralization. S(0) particles formed through this mechanism possess specific signatures such as morphologies that differ from that of their inorganically precipitated counterparts, encapsulation within an organic envelope, and metastable crystal structures (presence of the monoclinic β- and γ-S8 allotropes). Here, we investigated S(0) formation by the chemolithoautotrophic sulfur-oxidizing and nitrate-reducing bacterium Sulfuricurvum kujiense (Epsilonproteobacteria). We performed a thorough characterization of the S(0) minerals produced extracellularly in cultures of this microorganism, and showed that they present all the specific signatures (morphology, association with organics, and crystal structures) of organomineralized S(0). Using “spent medium” experiments, we furthermore demonstrated that soluble extracellular compounds produced by S. kujiense are necessary to form and stabilize S(0) minerals outside of the cells. This study provides the first experimental evidence of the importance of organomineralization in microbial S(0) formation. The prevalence of organomineralization in extracellular S(0) precipitation by other sulfur bacteria remains to be investigated, and the biological role of this mechanism is still unclear. However, we propose that sulfur-oxidizing bacteria could use soluble organics to stabilize stores of bioavailable S(0) outside the cells.